Regional Sovereign Funds and Prospects for Borrowing their Experience in Russia - Yu. P. Voronov (Мир новой экономики)
Possibility of regional sovereign funds world experience using in Russia is dealt with in article. It is expected that these funds resources might arise from three sources: part of mining revenues, part of land stock in government ownership and so called northern allowances following the example of Alaska. It is indicated that high proportion of land in government ownership does not contribute successfully to the development of region.